2016
DOI: 10.23910/ijbsm/2016.7.4.1531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inorganic Fertilizers and Organic Amendments on Plant Nutrients and Soil Enzyme Activities under Incubation

Abstract: An incubation experiment was carried out in the department of Soil Science and Agricultural Chemistry, ANGRAU, Hyderabad, India during 2013−14 with 12 treatments including control to study the mineralization pattern and timely release of nutrients (N, P, K and soil enzymes) to plant from different sources and periods. Mineralization of nitrogen (NH 4 +-N and NO 3-N), phosphorus (P 2 O 5) potassium (K 2 O) and soil enzymes (urease, acid and alkaline phosphatase and dehydrogenase) activities from different treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Maximum activity of acid and alkaline phosphatase was observed at 60 DAS due to increased root exudates production at critical crop growth stages. These results were supported by [23] who observed higher phosphatase activity during the initial days of incubation.…”
Section: Phosphatase Activitysupporting
confidence: 71%
“…Maximum activity of acid and alkaline phosphatase was observed at 60 DAS due to increased root exudates production at critical crop growth stages. These results were supported by [23] who observed higher phosphatase activity during the initial days of incubation.…”
Section: Phosphatase Activitysupporting
confidence: 71%
“…This might be due to higher microbial activity and availability of carbon substrate as compared to solitary application of fertilizers. Increase in DHA with addition of FYM was also reported in several studies (Bastida et al 2012, Srinivasan et al 2016. due to lack of sufficient substrate.…”
Section: Microbial Biomass Carbon (Mbc) and Microbial Biomass Nitroge...supporting
confidence: 66%
“…Under balanced fertilization, higher microbial population also resulted into more secretion of enzyme and increased activity. The higher APA under conjoint use of organic manures and NP fertilizers over NP fertilizer alone was also observed by Srinivasan et al (2016), Jia et al (2018). The lowest APA (572.25 µgPNP/g/h) was observed in plots treated with chemical fertilizers may be attributed to less substrate availability.…”
Section: Application Of Np Fertilizers Recorded Lowest Enzyme Activitymentioning
confidence: 70%
“…As shown in our previous recorded data [ 5 ] for macro and micronutrients analysis of FW, results showed that FW is rich in N (7.01%), P (12,201 µg/g), K (1573 µg/g), Ca (89,762.5 µg/g), Mg (189 µg/g), Fe (266.81 µg/g) and Zn (94.37 µg/g). Also, the increase in onion growth attributes due to FW application could be a result of increased phosphatase and chitinase activity [ 54 ].…”
Section: Resultsmentioning
confidence: 99%